PENERAPAN STRATEGI THINK TALK WRITE DALAM PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII2 SMP NEGERI 20 PEKANBARU - Rina Ayu Ramadhani; Rini Dian Anggraini; Suhermi Suhermi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This classroom action research is aimed at improving learning process and improving math learning outcomes achievement by applying think talk write strategy in the cooperative learning. The subject of this research is students of class VIII2 SMPN 20 Pekanbaru in academic year of 2015/2016, there are 40 students in the class, consist 17 boys and 23 girls. The research consist of two cycles in which each cycle consisted of four phases, i.e; namely planning, implementing, observing, and reflecting. By the end of a cycle, daily test was held. The data was collected by means of observation and daily test. The action success indicators were if there is learning process improvement and the increasing number of students passing Minimun Completeness Criteria (MCC) in daily test I and daily test II. The research shows that teachers and students’ activities were conducted well as planned. Most of the students participated actively in the learning process e.g. discussing, presenting student’s worksheet, responding to classmate’s presentation, and drawing the lesson conclusion. Additionally, the students afforded to answer the written test given by teacher well. Therefore, it can be said that improvement of learning process took place in every meeting. Furthermore, the number of students passing the MCC on base score, daily test I (first cycle), daily test II (second cycle) were respectively 40%, 50%, and 70%. The percentage of MCC achievement also indicates the increase after the implementation, thus it can be said that the students’ learning outcomes also increse. The result of research conclude that applying think talk write strategy in the cooperatif learning can improves mathematics achievement VIII2 SMPN 20 Pekanbaru.Key Words: Math Learning Outcomes, Think Talk Write Strategy in the Cooperative Learning, Classroom Action Research.